Recognition of Lewis x Derivatives Present on Mucins by Flagellar Components of Pseudomonas aeruginosa - Scharfman, Andree (American Society for Microbiology, 2001)
Pseudomonas aeruginosa binds to human respiratory mucins by mechanisms involving flagellar component-receptor interactions. The adhesion of P. aeruginosa strain PAK is mediated by the flagellar cap protein, FliD, without the involvement of flagellin. Two distinct types of FliD proteins have been identified in P. aeruginosa: A type, found in strain PAK, and B type, found in strain PAO1. In the present work, studies performed with the P. aeruginosa B-type strain PAO1 indicate that both the FliD protein and the flagellin of this strain are involved in the binding to respiratory mucins. Using polyacrylamide-based fluorescent glycoconjugates in a flow cytometry assay, it was previously demonstrated that P. aeruginosa recognizes Le(x) (or Lewis x) derivatives found at the periphery of human respiratory mucins. The aim of the present work was therefore to determine whether these carbohydrate epitopes (or glycotopes) are receptors for FliD proteins and flagellin. The results obtained by both flow cytometry and a microplate adhesion assay indicate that the FliD protein of strain PAO1 is involved in the binding of glycoconjugates bearing Le(x) or sialyl-Le(x) determinants, while the binding of flagellin is restricted to the glycoconjugate bearing Le(x) glycotope. In contrast, the type A cap protein of P. aeruginosa strain PAK is not involved in the binding to glycoconjugates bearing Le(x), sialyl-Le(x), or sulfosialyl-Le(x) glycotopes. This study demonstrates a clear association between a specific Pseudomonas adhesin and a specific mucin glycotope and demonstrates that fine specificities exist in mucin recognition by P. aeruginosa.